Understanding the strategic importance of indirect procurement - Kamperin, Axel; Kanmert, Jacob (My University, 2020)
Procurement has progressed in strategical importance, and plenty of resources and tools are used to generate effective sourcing of the required material. The area has received much attention from research, however, this research mainly focuses on the area of direct material, products and services directly contributing to creating the finished products or service. This leaves the area of indirect material and services as a less investigated topic, although it often totals to 40-50% of a company’s total spend. These costs include services such as consultants, travel and facility management and products like office equipment and utilities that are required to carry out the company’s operations and are very similar across different type of companies and industries. This study, therefore, aims to investigate the management of indirect spend at the MedTech company Dentsply IH AB in Mölndal and its two business units Wellspect Healthcare and Dentsply Sirona Implants. Qualitative and quantitative measures were taken to provide an outlook on the current state of spend and present processes within the subject. The results show that the indirect procurement within DIH is immature in that departments are uncoordinated and few standardised processes exist, a lack of quality and accessible data complicates getting an overview and controlling the spend and a large number of suppliers are used as a result. The final part of the study presents an analysis of the data to show potential improvement and synergies for and between the two business units. Suggestions on how to improve the procurement of indirect material and services within DIH and suggestions to capture identified synergies and a proposal on how to prioritise amongst projects is presented. The study’s findings were also found to be more generally applicable than first was thought, much due to the nature of indirect categories that could be confirmed from the case studied.
Keywords: procurement; purchasing; indirect materials and services; IDM; spend analysis